2022
DOI: 10.21203/rs.3.rs-1797700/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A pan-cancer analysis of the oncogenic role of 7-dehydrocholesterol reductase (DHCR7) in human tumors

Abstract: Background: DHCR7, a switch between cholesterol and vitamin D synthesis that plays a pivotal role in tumorigenesis, is a promising therapeutic target in oncology. Despite increasing strong support for its importance, there is no pan-cancer analysis across multiple databases that can be available for in-depth data mining of the gene. Methods: We first investigated the potential oncogenic roles of DHCR7 based on tumor data from both The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO). A variety of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…All the data to date would suggest that pronounced elevation of 7-DHC during development (through its oxysterols) is detrimental. In the field of cancer research, DHCR7 expression levels were found to be positively correlated with the infiltration of cancer-associated fibroblasts (CAFs) and myeloid-derived suppressor cells (MDSCs), and negatively correlated with anti-tumor immune cells in a majority of tumors [ 62 ]. For example, in pancreatic cancer, high DHCR7 gene expression results in shorter survival of patients [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the data to date would suggest that pronounced elevation of 7-DHC during development (through its oxysterols) is detrimental. In the field of cancer research, DHCR7 expression levels were found to be positively correlated with the infiltration of cancer-associated fibroblasts (CAFs) and myeloid-derived suppressor cells (MDSCs), and negatively correlated with anti-tumor immune cells in a majority of tumors [ 62 ]. For example, in pancreatic cancer, high DHCR7 gene expression results in shorter survival of patients [ 63 ].…”
Section: Discussionmentioning
confidence: 99%